2015
DOI: 10.1007/s10953-015-0389-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Speed and Related Thermo-acoustical Parameters of Solutions of 1,1′-Bis(3-methyl-4-ethoxyacetylphenoxy)cyclohexane at Four Different Temperatures

Abstract: The density (q), viscosity (g) and ultrasonic speed (U) of the pure solvents: 1,4-dioxane (DO), ethyl acetate (EA), tetrahydrofuran (THF) and solutions of the biologically active 1,1 0 -bis(3-methyl-4-ethoxyacetylphenoxy)cyclohexane were investigated at four temperatures: 298, 303, 308 and 313 K over a wide range of concentrations (0.1-0.01 molÁdm -3 ) to understand molecular interactions in these solutions. Various acoustical and thermodynamic parameters such as specific acoustical impedance (Z), isentropic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
6
6
0
Order By: Relevance
“…Several other authors [ 148 , 156 , 179 ] used the same vibrating-tube apparatus and obtained consistent results with the measurements of Vercher et al [ 198 ]. The main contributor to the uncertainty estimate of these apparatuses is the recommended value of at least 0.03 from Prokopová et al [ 202 ] that was applied to the data of Dhaduk et al [ 148 ], Ivanov [ 156 ], and Piñeiro et al [ 179 ].…”
Section: Validation Of the Eos With Literature Datasupporting
confidence: 78%
“…Several other authors [ 148 , 156 , 179 ] used the same vibrating-tube apparatus and obtained consistent results with the measurements of Vercher et al [ 198 ]. The main contributor to the uncertainty estimate of these apparatuses is the recommended value of at least 0.03 from Prokopová et al [ 202 ] that was applied to the data of Dhaduk et al [ 148 ], Ivanov [ 156 ], and Piñeiro et al [ 179 ].…”
Section: Validation Of the Eos With Literature Datasupporting
confidence: 78%
“…Similar results have been reported by other workers [52]. Thus, increase in the internal pressure and decrease of free volume indicate increase the cohesive forces in the solution [53]. The increase in temperature has two opposing effects, namely structure formation (intermolecular association) and structure destruction.…”
Section: Comparison Of Figures 5 [A] and [B]supporting
confidence: 89%
“…Relative deviations of the experimental viscosity data with the calculated results from the Tait–Andrade model for ETA as a function of the temperature (left panel) and pressure (right panel). Brown triangles, Djojoputro and Ismadji; green triangles, Aminabhavi et al; red circles, Aminabhavi et al; blue squares, Pal and Kumar; blue triangles, Sastry et al; green triangles, Dhaduk et al; □, this work.…”
Section: Discussionmentioning
confidence: 63%
“…Available literature data on the viscosity of ETA and DES are compared with the Tait–Andrade models, as shown in Figures and . Djojoputro and Ismadji, Aminabhavi et al, , Pal and Kumar, Sastry et al, and Dhaduk et al only experimental studied the liquid viscosity of ETA under atmospheric pressure. Among them, the ETA data from Djojoputro and DES data from Ismadji and Aminabhavi et al generally indicated a temperature-related deviation trend but still fell in a reasonable range (2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation